Household food and water insecurity and its association with diarrhoea, respiratory illness, and stunting in Ecuadorian children under 5 years - Rishika Chakraborty; Rodrigo X. Armijos; Erika T. Beidelman; Molly Rosenberg; M. Margaret Weigel (Wiley, 2024)
Abstract Household food and water insecurity has been previously associated with adverse health consequences in children. However, these relationships are understudied in middle‐income Latin American populations such as in Ecuador, where a high prevalence of food and water insecurity has been reported. Using cross‐sectional data from 2018 Ecuadorian National Health and Nutrition Survey, we examined the association of household food insecurity (HFI), household water insecurity (HWI), and concurrent HFI‐HWI with diarrhoea, respiratory illness (RI), and stunting in 20,510 children aged ≤59 months. HFI was measured using the Food Insecurity Experience Scale. HWI was defined when households responded negatively to one or more of four drinking water indicators. Maternal caregivers reported on child diarrhoea and RI episodes during the previous 2 weeks. Measured length or height was used to assess stunting. We constructed log‐binomial regression models to estimate the associations of HFI, HWI, and concurrent HFI‐HWI with child outcomes. Moderate‐severe HFI was associated with a higher prevalence of diarrhoea (PR = 1.39; 95% CI: 1.18, 1.63) and RI (PR = 1.34; 95% CI: 1.22, 1.47), HWI with a higher prevalence of RI (PR = 1.13; 95% CI: 1.04, 1.22), and concurrent HFI‐HWI with a higher prevalence of diarrhoea (PR = 1.30; 95% CI: 1.05, 1.62) and RI (PR = 1.45; 95% CI: 1.29, 1.62). Stunting was not associated with HFI, HWI nor concurrent HFI‐HWI. These findings suggest that HFI and HWI can independently and jointly act to negatively affect children's health. Policies and interventions aimed at alleviating both food and water insecurity are needed to bring sustained health improvements in Ecuadorian children.